KETIDAKADILAN SOSIAL DALAM PERSPEKTIF SILA KELIMA PANCASILA - Ertika Susanti Pasaribu (Publikasi Inspirasi Indonesia, 2024)
Social justice in the Indonesian context is a complex and multidimensional struggle, including the protection of rights, equality, general welfare, and proportionality between individual, social and state interests. The main goal is to create social welfare for all citizens through equal distribution of resources, reducing socio-economic disparities, and ensuring a decent life in accordance with human dignity. Social justice in Indonesia also includes eliminating discrimination and inequality, which are challenges in creating a just and inclusive society. To achieve social justice, comprehensive efforts are needed that involve increasing awareness, developing supporting policies and programs, and fair law enforcement. This research uses a literature-based qualitative approach to analyze official documents related to social justice policies, laws and practices. The research results show that the principles of social justice can be implemented through the active participation of civil society, the development of policies that support equality, and the active role of government and non-governmental organizations. In conclusion, achieving better social justice in Indonesia requires the cooperation of various parties to ensure that the principles of social justice are implemented effectively in various aspects of society.